Does intermittent hypoxic exposure enhance the cardioprotective effect of exercise in an inactive population? - Lizamore, Catherine A.; Stoner, Lee; Kathiravel, Yaso; Elliott, John; Hamlin, Michael J. (Frontiers in Physiology, 2022)
The aim of this study was to determine whether exercise supplemented with passive intermittent hypoxic exposure (IHE) improved overall cardiovascular disease risk and individual risk factors. Participants were randomized to exercise-only (Ex, n = 18, 5 males, 13 females; age: 56.4  6.5 years; weight: 81.2  15.9; height: 167.3  8.42) or exercise + IHE (IHE + Ex, n = 16; 6 males, 10 females; age: 56.7  6.4 years; weight: 78.6  12.4 kg; height: 168.0  8.8 cm). Both groups received the same strength and aerobic exercise training (1 hr, 3 d/wk, 10 wks). IHE + Ex also received IHE (5 min hypoxia: 5 min ambient air x 6) for 2-3 d/wk. Measurements were collected before (Baseline), after (Post), and 4- and 8-wks following the intervention. There were small, beneficial reductions in overall 5- year cardiovascular risk in both groups. At Post, for IHE + Ex compared to IHE there were unclear to likely improvements in high density lipoprotein (8.0  8.0%), systolic blood pressure (-3.4  3.4%) and V˙O2peak (3.1  7.7%). These improvements persisted at 8-wk. There was an unclear improvement in arterial wave reflection (augmentation index) at Post (-6.1  18.4%, unclear), but became very likely harmful at 8-wk (8-wk: 24.8  19.7%). The conflicting findings indicate that in inactive adults, the addition of IHE to exercise may be beneficial to systemic markers of cardiovascular health but may also increase myocardial load due to increased arterial wave reflection.